Ultrasound-guided modified thoracoabdominal nerve block for postoperative analgesia in laparoscopic renal cyst decompression: a randomized double-blind controlled trial - Wan, Mengning; Dong, Jun; Wei, Ke; Jin, Juying; Cao, Jun; Yuan, Baohong (Frontiers in Medicine, 2025)
BackgroundLaparoscopic renal cyst decompression (LRCD) is a common procedure in urology, but postoperative pain remains a significant challenge. While regional nerve blocks provide more targeted pain relief, there is no universally accepted pain management strategy for LRCD. The ultrasound-guided modified thoracoabdominal nerve block (M-TAPA) may offer effective analgesia by blocking the anterior and lateral branches of the intercostal nerves (T5-T12). However, its efficacy in LRCD has not been thoroughly evaluated.ObjectiveThis study aimed to assess the efficacy and safety of unilateral M-TAPA in reducing postoperative pain and opioid consumption in patients undergoing LRCD, and to evaluate its potential benefits in enhancing recovery.MethodsIn this randomized, double-blind, controlled trial, 61 patients undergoing LRCD were assigned to either the M-TAPA group (n = 31) or the Control group (n = 30). The M-TAPA group received ultrasound-guided nerve block, while the Control group received a placebo injection. Postoperative pain was assessed using the numerical rating scale (NRS) over a 48-h period. Additional outcomes included opioid consumption and opioid-related side effects, such as nausea and vomiting.ResultsThe M-TAPA group had significantly lower NRS scores at all time points compared to the Control group, with the largest difference observed at 6 h postoperatively (4.27 ± 0.83 in the Control group vs. 2.19 ± 0.54 in the M-TAPA group). Repeated measures ANOVA revealed a significant interaction between time and treatment (F = 20.813, p < 0.001). Opioid consumption was reduced by 22% in the M-TAPA group over 48 h (p < 0.001), and the need for antiemetic drugs was significantly lower (p = 0.020). No M-TAPA-related complications were observed.ConclusionM-TAPA was found to be an effective method for reducing postoperative pain and opioid consumption in patients undergoing LRCD.Clinical Trial Registrationwww.chictr.org.cn.